Pelaksanaan Perampasan Aset Terpidana Tindak Pidana Korupsi dalam Hal Pemenuhan Uang Pengganti terhadap Objek Jaminan Hak Tanggungan Perbankan (Studi Kasus Perkara Putusan Nomor 30/Pid.Sus.Tpk/2023/Pn.Tjk) - M. Yudhi Guntara Eka Putra; Maroni Maroni; Rinaldy Amrullah (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
The enforcement of court decisions in corruption cases often faces legal and practical challenges, particularly when the convict’s assets are pledged as collateral under banking security rights. This study aims to examine how asset confiscation in corruption cases is carried out by the Prosecutor’s Office in fulfilling compensation payments when the assets are bound by mortgage rights, as well as to identify the inhibiting factors. Using a normative and empirical juridical approach, data were collected through literature studies and field interviews with prosecutors and criminal law scholars. The findings reveal that asset confiscation is constrained when the identified property has been mortgaged to a bank, as banking security rights provide legal protection to third parties acting in good faith. Consequently, the prosecutor cannot execute the asset to cover the compensation amounting to IDR 284,916,038, and the convict must instead serve an additional one-year imprisonment as ordered by the court. The main obstacles include substantive legal limitations, the absence of regulatory instruments for installment payments of compensation, and the convict’s preference to serve substitute imprisonment rather than paying compensation.